Obesity in the world - Malo Serrano, Miguel (2017)
This article discusses overweight and obesity and its implications as a huge public health problem in the world and in Peru. It is a problem with rapid growth in recent decades, particularly among younger age groups, and is related to changes in the living conditions of the population. Notable among these changes are the market’s massive growth and the consumption of ultra-processed products, which are gradually replacing natural and minimally processed foods in the population’s diet. The article argues that this growth is mainly due to two factors: the market`s lack of regulation for these ultra-processed products and the huge marketing machinery that encourages their consumption. Obesity is also related to the urbanization process. The latter has given rise to cities that prioritize motorized mobility at the expense of non-motorized transportation, with insufficient green areas and recreation spaces, all of which decreases the population’s physical activity levels. In order to address this enormous health problem, the international community has responded with various documents that compile well evidence based policy recommendations to control obesity and its consequences on noncommunicable diseases. Finally, the article remarks the fact that these policies confront powerful economic interests from the food and beverage industry that hinder their implementation. It depends on policy makers and citizens to surmount this conflict of interests and tip the balance towards the health of the population.